Association of Estrus Expression Preceding Timed-Artificial Insemination and Fertility in Dairy Cattle - M. Schultz; J. S. Stevenson; V. E. Gomez-Leon (Kansas Agricultural Experiment Station Research Reports, 2025)
The aim of this study was to evaluate the association between estrus expression and fertility outcomes in nulliparous Holstein heifers and high-producing lactating dairy cows submitted to GnRH-based timed artificial insemination (TAI) protocols. Retrospective data from the Kansas State University Dairy Teaching and Research Center from 2021 to 2024 were used in the study. Data included 1,154 first-service breeding records, 359 estrus events, pregnancy diagnoses, and calving incidence. Estrus’s expression was recorded using automated activity monitors. Estrus incidence, intensity, duration, and timing were analyzed in relation to pregnancy per artificial insemination (P/AI) and calving risk with Generalized Linear Models in SAS. Parity (heifer, primiparous, and multiparous) was included in the statistical model. Heifers exhibited higher estrus incidence, intensity, and duration compared to primiparous and multiparous cows. While intensity and duration did not directly impact P/AI, the timing of estrus expression significantly influenced outcomes, with animals expressing estrus closer to insemination (within 18 hours) demonstrating greater odds of pregnancy. Moreover, estrus expression was associated with a 15% increase in P/AI and improved calving rates (93% vs. 87%) regardless of parity (heifer, primiparous, or multiparous). Although previous studies have shown that estrus expression in high-producing cows may be detrimental or unnecessary for fertility at first service, our findings suggest that promoting estrus expression during TAI protocols may be beneficial. Future research should corroborate our findings, explore strategies to promote estrus expression during TAI, and assess the physiologic mechanisms leading to higher fertility in animals expressing estrus.
Keywords: estrus; timed artificial insemination; fertility; dairy; pregnancy per artificial insemination